Preliminary Study on Access to Health Services for Elderly Women: The Age and Socio-Economic Issues of Elderly Women in Pancuran Village, Salatiga - Sanubari, Theresia Pratiwi Elingsetyo; Yaniariyani, Catherina Frisca (Jurnal Perempuan, 2019)
The increasing number of elderly people from year to year shows the high life expectancy in elderly women. This situation coupled with cultural and social aspects can trigger vulnerability for elderly women, including the health aspect. This study aims to describe the factors of access to health services for elderly women in the village of Pancuran, Salatiga. The method used is descriptive-quantitative with data collection carried out in Pancuran Village using a questionnaire. Elderly women in Pancuran Village have different economic, educational, employment and social status backgrounds but have the same vulnerability to access health services due to the unavailability of posyandu for the elderly in Pancuran Village. Nevertheless, efforts to access health services are still underway. This research shows that cultural involvement in health care is needed to realize integrated, patient-centered, and gender-friendly health services.